2-D coupled fluid-particle numerical analysis of seepage failure of saturated granular soils around an embedded sheet pile with no macroscopic assumptions. (August 2021) - Fukumoto, Yutaka; Yang, Hongxuan; Hosoyamada, Tokuzo; Ohtsuka, Satoru
Graphical abstract: Abstract: The present paper reports the application of a 2-D coupled fluid-particle simulation model with no macroscopic assumptions to the seepage failure of saturated granular soils. The basic problem of the seepage failure of a horizontal ground with an embedded sheet pile, where the system size is set to be 200 × 100 mm and the average diameter of the soil particle is 550 μ m, is numerically investigated. Both the seepage flow and the motion of the soil particles are directly solved by coupling the lattice Boltzmann method and the discrete element method. The goal of this study is to confirm that the 2-D direct simulation can be performed on the scale of a model experiment with soil particles that correspond in size to that of real sand. As a result of the analysis, it is shown that a typical series of behavior for seepage failure, where boiling and heaving initially occur on the downstream side near the sheet pile and finally lead to quicksand, can be seamlessly reproduced. Comparing the cases with different initial void ratios, it is found that the deformation area and the rates of the failure process can be varied according to the packing state. By tracking the velocity of each soil particle, it is visually shown that seepage failure begins to occur in the corner areas of the sheet pile much earlier than the onset of quicksand. By focusing on the fluid force acting on that particle, it is seen that the relatively large values for the hydrodynamic forces are concentrated on the upstream side before the beginning of uplift. In addition, by a comparison with two theories for the critical hydraulic gradient, the current limitations and problems of the proposed method are also summarized.